INCIDENCE OF OPERCULAR ULCER DISEASE IN LABEO ROHITA (HAM.) - Lipton, A P (Indian Journal of Fisheries, 2011)
Ulcer disease causes heavy mortality in Japan to carps, coloured carpsand gold fish and it is ranked as one of the major epidemics (Kawatsu et al1979). It is also reported from the northeastern United States and Canada, whereit was found to affect the salmonid fishes (Sarig 1979, Bullock et al 1971),whereas in India the ulcer disease is not very common (Gopalakrishnan 1963).In all these cases ulcers were reported to erode the body surface, fins or mouth(Ronald et al 1980). So far, no record is available on the occurrence of ulceron the opercular region.